Experimental study and Large Eddy Simulation of thermal mixing phenomena of a parallel jet with perforated obstacles - Varol, Yasin; Kok, Besir; Ayhan, Huseyin; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2017)
Thermal mixing and flow field due to two parallel jets which have different temperatures are investigated both experimentally and numerically. The perforated passive obstacles are used with different geometrical specifications. They are located in front of the jets to control flow field and mixing behavior of the jets. An experimental setup designed and manufactured and Large Eddy Simulation turbulence model with the WALE subgrid-scale stress model were used to simulate same experimental conditions. Three perforated obstacles (POs) with different porosity values were used in the study and these obstacles inserted into a rectangular cross-section confined channel. Results demonstrated that increasing the values of temperature differences enhance thermal mixing performance along the channel. The best mixing quality was captured at the same flow rates of the jets. The perforated obstacle has significant positive effect on the mixing performance and this effect increase with higher porosity values. Dominant frequency of mixing region was found as 5 Hz in all cases. The temperature profiles showed that as porosity decreases thermal oscillations are starting to reach the wall. Both 2D and 3D velocity profiles demonstrated that using of POs reduces the domination of turbulence area in the channel. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Parallel jet; Perforated obstacle; Heat transfer; LES; Thermal mixing